2003
DOI: 10.1177/0091270003043006008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Intrathecal Ziconotide in Chronic Pain Patients

Abstract: The pharmacokinetics and pharmacodynamics of ziconotide were assessed over a 48-hour period following intrathecal (i.t.) administration (1, 5, 7.5, or 10 micrograms) to 22 patients with chronic, nonmalignant pain. Plasma and cerebrospinal fluid (CSF) samples were obtained over a 24-hour period. Analgesic efficacy was monitored using Visual Analog Scale of Pain Intensity (VASPI) and Category Pain Relief Scores (CPRS) measurements. Pharmacokinetic (PK) parameters were calculated by noncompartmental methods. Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 0 publications
1
41
1
1
Order By: Relevance
“…For example, delivery of conotoxins to the intrathecal space could, in principle (on the basis of limited redistribution because of their peptidic nature), avoid side effects resulting from on-target effects at different sites. In addition, once delivered to these compartments, it seems that many conotoxins are surprisingly stable, with half-lives of hours or more, rather than minutes (Wermeling et al, 2003;Kern et al, 2007). For example, a relatively long half-life in cerebrospinal fluid may also account for the extended duration of action observed after intrathecal dosing of Xen2174 (Lewis, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, delivery of conotoxins to the intrathecal space could, in principle (on the basis of limited redistribution because of their peptidic nature), avoid side effects resulting from on-target effects at different sites. In addition, once delivered to these compartments, it seems that many conotoxins are surprisingly stable, with half-lives of hours or more, rather than minutes (Wermeling et al, 2003;Kern et al, 2007). For example, a relatively long half-life in cerebrospinal fluid may also account for the extended duration of action observed after intrathecal dosing of Xen2174 (Lewis, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The search identified that the Visual Analogue Scale for Pain Intensity (VAS-PI) was used frequently to measure the different severities of pain, and its reliability for assessing chronic pain has been demonstrated in previous studies [14,15]. The VAS-PI score was used as the primary end point in a number of studies assessing the efficacy of IT ziconotide administered in severe chronic pain [16][17][18][19][20] and in this study it was used to define the core HSs into four levels of severity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, another mechanism can theoretically be accountable for drug lifetimes in CSF. Pharmacokinetic studies of ziconotide (MVIIA) in chronic pain patients suggest that the main pathway for ziconotide clearance is the bulk redistribution of CSF (Wermeling et al, 2003). A later study using a canine model came to a similar conclusion for ziconotide clearance (Yaksh et al, 2012).…”
Section: Figurementioning
confidence: 95%
“…Only a limited amount of data is available on the bioavailability and stability of clinically used ziconotide in plasma or CSF (Newcomb et al, 2000;Wermeling et al, 2003;Yaksh et al, 2012). In our study, the proteolytic stability of CVID, CVIE&F and their analogues was investigated in human serum since it incorporates a highly active mixture of proteases that provides a robust 'test' of peptide stability.…”
Section: Figurementioning
confidence: 99%